A Predictive Simulation and Optimization Architecture based on a Knowledge Engineering User Interface to Support Operator 4.0. Issue 1 (2021) - Palasciano, Claudio; Toscano, César; Arrais, Rafael; Sobral, Narciso Manuel; Floreani, Fabio; Sesana, Michele; Taisch, Marco
Abstract: The Real-Time Monitoring and Performance Management suite tool, known as UIL (User Interface Layer), was developed in the FASTEN project, a R&D initiative financed by the innovation and research program H2020 within a bilateral Europe-Brazil call. UIL was conceived and deployed in the IIoT architecture of the project. The goal was to provide a user-centered assistance to the human operator for both decision-responsibility and control loop, in a continuously updating information fashion, related to system's state. In order to have experimental results, a qualitative assessment was conducted in an industrial environment. The architecture proposed was based on the adoption of a Knowledge Engineering User Interface to support Operator 4.0. Our empirical experiments point out to a successful set of results.